Unsur Intrinsik Naskah Drama “Perempuan dan Ilusinya” Karya Adhyra Pratama: Kajian Struktural - afriany, fany (Jurnal Pena Indonesia, 2023)
This study took the script of the drama "Perempuan dan Ilusinya" by Adhyra Pratama. With the object of research in the form of analysis of intrinsic elements that exist in the play. The research Model used in this study is qualitative with descriptive data. The data in this study were collected by listening and recording techniques. Primary data sources obtained from the observation and mutilation of drama script "Perempuan dan Ilusinya" by Adhyra Pratama. Meanwhile, secondary or supporting data obtained from literature studies on relevant research. The results obtained from this study are (1) theme; (2) Plot; (3) characters and characterizations; (4) setting; (5) point of view; (6) the mandate in the drama script "Perempuan dan Ilusinya" and illusion by Adhyra Pratama. Keywords: Drama, Literature, Objective, Perempuan dan Ilusinya, Structural